The Relationship Between Obesity and Depression in Ukrida Medical Students - Johannes Hudyono; Judin Purba Tanjung; Donna Mesina Rosadini Pasaribu; Inggrid Osya Far Far; Rizka Chairani (Jurnal MedScientiae, 2023)
Not just obesity can cause a lot of trouble for physical health such as hypertension, dyslipidaemia, and diabetes, but also can cause problem for mental health such as depression. According to studies this can be an indirect cause that leads them to the depression state. Using analytic research, the aim in this study was to see whether there is a relationship between obesity and depression in medical students of Ukrida batch 2013 or not. Sample taken by purposive sampling technique and data retrieved by using PHQ-9 as a questionnaire to rate the students depression score and measure their body mass index to see their nutritional status. The result from the study were 21,5 % of total respondents with normal BMI and no depression, 28,5% with normal BMI and depression, 25,4% with obese BMI and no depression, and 24,6% obese BMI and depression. This study concluded that there was no significant relationship between obesity and depression in medical student of Ukrida batch 2013 (p value 0.380).